Nanoparticles based on the zwitterionic pillar[5]arene and Ag+: synthesis, self-assembly and cytotoxicity in the human lung cancer cell line A549 - Shurpik, Dmitriy N.; Sevastyanov, Denis A.; Zelenikhin, Pavel V.; Padnya, Pavel L.; Evtugyn, Vladimir G.; Osin, Yuriy N.; Stoikov, Ivan I. (Beilstein Journal of Nanotechnology, 2020)
For the first time, stable pillar[5]arene/Ag+ nanoparticles, consisting of water-soluble pillar[5]arene containing γ-sulfobetaine fragments and Ag+ ions without Ag–Ag bonds, were synthesized and characterized. The pillar[5]arene/Ag+ (ratio 1:10) nanoparticles obtained were cubic with a rib length of 100 nm and are less cytotoxic than Ag+ ions. The survival of the A549 model cells in the presence of pillar[5]arene/Ag+ (1:10) nanoparticles at a concentration of 30 and 40 μM was 76% and 55%, while in the absence of pillar[5]arene, the cell survival for free Ag+ ions at the same concentration was 30% and 10%, respectively. The results can be used to create new antibacterial materials and 2D biomedical coatings.
Keywords: cytotoxicity; macrocyclic receptors; nanoparticles; pillar[5]arene; self-assembly; silver